The constitutional gain‐of‐function variant p.Glu1099Lys in NSD2 is associated with a novel syndrome. Issue 2 (20th October 2022) - Popp, Bernt; Brugger, Melanie; Poschmann, Sibylle; Bartolomaeus, Tobias; Radtke, Maximilian; Hentschel, Julia; Di Donato, Nataliya; Rump, Andreas; Gburek‐Augustat, Janina; Graf, Elisabeth; Wagner, Matias; Sorge, Ina; et al.
Abstract: NSD2 dimethylates histone H3 at lysine 36 (H3K36me2) and is located in the Wolf‐Hirschhorn syndrome (WHS) critical region. Recent descriptions have delineated loss‐of‐function (LoF) variants in NSD2 with a distinct disorder. The oncogenic missense variant p.Glu1099Lys occurs somatically in leukemia and has a gain‐of‐function (GoF) effect. We describe two individuals carrying p.Glu1099Lys as heterozygous de novo germline variant identified by exome sequencing (ES) of blood DNA and subsequently confirmed in two ectodermal tissues. Clinically, these individuals are characterized by intellectual disability, coarse/ square facial gestalt, abnormalities of the hands, and organomegaly. Public cell lines with NSD2 GoF variants had increased K36me2, DNA promoter methylation, and dysregulated RNA expression. NSD2 GoF caused by p.Glu1099Lys is associated with a novel phenotype different from WHS and Rauch–Steindl syndrome (RAUST). Abstract : The gain‐of‐function variant p.Glu1099Lys in NSD2 was described in hematologic malignancies while germline loss‐of‐function was associated with Wolf–Hirschhorn syndrome and Rauch–Steindl syndrome. Now we associate this variant identified in the germinal of two individuals with a novel syndrome characterized by intellectual disability, coarse/ square face, hand abnormalities, and organomegaly.